Terrein suppressed lipopolysaccharide-induced neuroinflammation through inhibition of NF-κB pathway by activating Nrf2/HO-1 signaling in BV2 and primary microglial cells - Kwan-Woo Kim; Hye Jin Kim; Jae Hak Sohn; Joung Han Yim; Youn-Chul Kim; Hyuncheol Oh (Journal of Pharmacological Sciences, 2020)
In the course of our continuous investigation on the bioactive marine-derived fungal metabolites, terrein was isolated from marine-derived fungal strain Penicillium sp. SF-7181. Terrein inhibited the overproduction of pro-inflammatory mediators, such as nitric oxide (NO) and prostaglandin E2 (PGE2), as well as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in lipopolysaccharide (LPS)-stimulated BV2 and primary microglial cells. This compound also repressed the LPS-induced production of pro-inflammatory cytokines, interleukin (IL)-1β and IL-6. These inhibitory effects of terrein were associated with the inactivation of the nuclear factor kappa B (NF-κB) pathway through suppression of the translocation of p65/p50 heterodimer into the nucleus, the phosphorylation and degradation of inhibitor kappa B (IκB)-α and the DNA binding activity of the p65 subunit. In addition, terrein induced the protein expression of heme oxygenase (HO)-1 through the activation of nuclear transcription factor erythroid-2 related factor 2 (Nrf2) in BV2 and primary microglial cells. The anti-inflammatory effect of terrein was blocked by pre-treatment with a selective HO-1 inhibitor, suggesting that its anti-neuroinflammatory effect is mediated by HO-1 induction.